2006
DOI: 10.1002/ajh.20826
|View full text |Cite
|
Sign up to set email alerts
|

Hb J Meerut, a fast‐moving hemoglobin—a study of seven cases from India and a review of literature

Abstract: Fast-moving hemoglobins (FMH) are rare abnormal hemoglobin variants which migrate anodal to hemoglobin A on alkaline agarose gel electrophoresis. Only five cases of Hb J Meerut, an alpha variant FMH, have been reported so far. We here report seven cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Abnormal Hb should be considered when a major discrepancy is seen between levels of Hb A1c and fasting blood sugar values. In India, Hb J-Meerut has been reported in north Indian population [1,6]. To the best of authors' knowledge, this is the first case to be reported from a south Indian family.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Abnormal Hb should be considered when a major discrepancy is seen between levels of Hb A1c and fasting blood sugar values. In India, Hb J-Meerut has been reported in north Indian population [1,6]. To the best of authors' knowledge, this is the first case to be reported from a south Indian family.…”
Section: Discussionmentioning
confidence: 68%
“…They all have an electrophoretic mobility 'faster' than Hb A on cellulose acetate in common [1,2]. The fast moving nature of these Hb variants result from substitution of a negatively charged amino acid residue in either α, β or γ globin gene [1]. For e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This variant is very uncommon with only few cases reported worldwide. [14][15][16] A community based study in 3 districts of West Bengal namely Burdwan, 24 Parganas (North) and Midnapore (undivided) the prevalence rate of carrier state among antenatal mothers was found to be 5.95%. [7] The present study lacked the provision to rule out nutritional anemia in all cases by assay of serum iron, vitamin B12 and folate levels.…”
Section: Discussionmentioning
confidence: 99%